Bilateral Simultaneous Rupture of the Quadriceps Tendon in a Healthy Elderly Woman: A Case Report - Utomo, Pamudji; Adriansyah, Denny (Indonesian Journal of Medicine, 2019)
Background: Quadriceps tendon ruptures are uncommon injury that affects middle-aged women, predominantly it affects middle aged men. However, the bilateral quadriceps tendon rupture is extremely rare in the absence of systemic disease.Subjects and Method: We reported a case of bilateral quadriceps tendon rupture in a healthy 65 year old female. She felt pain in both knees since 4 months before entering the hospital. Local physical examination on both knees reveal the loss of normal contour of rectus femoris, tenderness at superior pole patella the ruptur site, and palpable defect within 2 cm of superior pole patella. Patient unable to extend knee against resistance, and unable to perform straight leg raise. The patient was carried out a surgical repair with consent.Results: After the surgery both knees were immobilized with knee extension splint for 6 weeks. Patient evaluation revealed no pain and progressive recovery of muscular strength after four months and could be able to walk and returned to normal activity.Conclusion: Surgery is needed to repair quadriceps rupture.Keywords: Quadriceps tendon, quadriceps rupture, repair tendon.Correspondence: Pamudji Utomo. Faculty of Medicine, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta, Central Java, Indonesia. Email: utomodr@yahoo.com.Indonesian Journal of Medicine (2019), 4(1): 54-58https://doi.org/10.26911/theijmed.2019.04.01.09